2020
DOI: 10.1186/s12889-020-09064-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations of physical partner violence and sexual violence victimization on health risk behaviours and mental health among university students from 25 countries

Abstract: Background: The study aimed to investigate the associations between physical partner violence victimization (IPV) and/or sexual violence victimization and various health risk behaviours and mental health in university students in 25 countries. Methods: Using a cross-sectional study design, 18,335 university students with a median age of 20 years from 25 countries in Africa, the Americas and Asia, replied to self-reported measures of interpersonal violence, health compromising behaviours, mental health measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
2
26
0
9
Order By: Relevance
“…It was developed in English, and then translated and back-translated into the languages of the study country following scientific procedures. The study response rate was more than 90% in most countries [14,15].…”
Section: Study Population and Proceduresmentioning
confidence: 94%
“…It was developed in English, and then translated and back-translated into the languages of the study country following scientific procedures. The study response rate was more than 90% in most countries [14,15].…”
Section: Study Population and Proceduresmentioning
confidence: 94%
“…In terms of SRH knowledge and services, low knowledge about HIV/AIDS transmission and negative attitudes about people with HIV/AIDS were associated with NMSV, as were higher fertility preferences than that reported by Indian women as whole [12] . Health knowledge and health care access, media access, and menstrual hygiene access and use were also associated with NMSV, as were tobacco and alcohol use, the latter findings seen in prior research with adolescents from other country contexts [32] , [33] , [34] , [35] but not previously identified in India. Research documents alcohol use as both a risk factor for sexual violence and a coping mechanism subsequent to such violence [35] .…”
Section: Discussionmentioning
confidence: 49%
“…Mahenge and colleagues in Tanzania also found higher levels of PTSD among pregnant women who had experienced intimate partner violence [ 103 ]. A multicountry study among university students from 25 countries (7 countries from sub-Saharan Africa) also suggested that PTSD was associated with intimate partner violence in all of the sub-Saharan African countries [ 104 ].…”
Section: Discussionmentioning
confidence: 99%